2010
DOI: 10.1002/anie.201000517
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Pummerer Reaction: Recent Developments in Thionium Ion Chemistry

Abstract: Since the early 1960s the Pummerer reaction has evolved to become an indispensable tool for synthesis, and continues to serve as a source of inspiration for organic chemists. In recent years, many exciting advances have demonstrated the broad scope and synthetic utility of Pummerer methodology and the versatility of thionium ion intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
102
1
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(116 citation statements)
references
References 54 publications
1
102
1
12
Order By: Relevance
“…Reaction with acetoxyacetyl chloride followed by ester hydrolysis proceeds in good yield to give the 1,4‐bis(hydroxyacetamide) 4 . Swern oxidation affords the 1,4‐bis(glyoxamide), which then undergoes a two‐directional Pummerer‐type12 cyclization as previously developed by Procter et al13 to close the intermediate tricycle 5 . Reductive cleavage of the sulfanyl groups by samarium iodide14, 15 completes the DPID core ( 6 ).…”
Section: Resultsmentioning
confidence: 90%
“…Reaction with acetoxyacetyl chloride followed by ester hydrolysis proceeds in good yield to give the 1,4‐bis(hydroxyacetamide) 4 . Swern oxidation affords the 1,4‐bis(glyoxamide), which then undergoes a two‐directional Pummerer‐type12 cyclization as previously developed by Procter et al13 to close the intermediate tricycle 5 . Reductive cleavage of the sulfanyl groups by samarium iodide14, 15 completes the DPID core ( 6 ).…”
Section: Resultsmentioning
confidence: 90%
“…Previously, we developed a highly efficient one‐pot synthesis of NH ‐1,2,3‐triazoles . With the available NH ‐1,2,3‐triazoles and our continuous studies on 1,2,3‐triazole and related chemistry, herein we reported a P 2 O 5 ‐mediated synthesis of N 1 ‐ and N 2 ‐substituted sulfur‐containing triazoles via a variant Pummerer rearrangement reaction between NH ‐1,2,3‐triazoles and DMSO (Scheme c). The Pummerer rearrangement reaction is a very powerful protocol for the construction of thioethers, and we proposed that NH ‐1,2,3‐triazoles could serve as effective nucleophiles to trap the thionium intermediates in the Pummerer rearrangement, which could give the S‐containing 1,2,3‐triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…This umpolung strategy couples two carbon sites that are inherently nucleophilic and delivers C3-arylated and the more challenging C3-alkylated benzothiophenes under mild conditions, with broad scope. The reaction operates via activation of the S–O bond in benzothiophene S -oxides 1 for an interrupted Pummerer reaction31 with phenol, or allyl- or propargyl-silanes to form intermediates I and II , which are predisposed for charge accelerated [3,3]-sigmatropic rearrangement32, resulting in C–C bond formation, therefore delivering the coupling partner in a perfectly site-selective manner.…”
mentioning
confidence: 99%